2017
DOI: 10.1021/acs.jmedchem.7b00360
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Irreversible Covalent FGFR Inhibitor 8-(3-(4-Acryloylpiperazin-1-yl)propyl)-6-(2,6-dichloro-3,5-dimethoxyphenyl)-2-(methylamino)pyrido[2,3-d]pyrimidin-7(8H)-one (PRN1371) for the Treatment of Solid Tumors

Abstract: Aberrant signaling of the FGF/FGFR pathway occurs frequently in cancers and is an oncogenic driver in many solid tumors. Clinical validation of FGFR as a therapeutic target has been demonstrated in bladder, liver, lung, breast, and gastric cancers. Our goal was to develop an irreversible covalent inhibitor of FGFR1-4 for use in oncology indications. An irreversible covalent binding mechanism imparts many desirable pharmacological benefits including high potency, selectivity, and prolonged target inhibition. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…In contrast, the control FGFR inhibitor BGJ398 failed to sustain inhibition of FGFR, which is consistent with its reversible noncovalent binding mechanism (Supplementary Table S1). We have also previously shown that PRN1371 demonstrates time-dependent enzyme inhibition of FGFR1-4 and sustains inhibition of fluorescent probe binding to the FGFR active site, further validating covalent FGFR engagement (8). CSF1R, the only kinase outside the FGFR family inhibited by PRN1371, was also studied using dialysis.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In contrast, the control FGFR inhibitor BGJ398 failed to sustain inhibition of FGFR, which is consistent with its reversible noncovalent binding mechanism (Supplementary Table S1). We have also previously shown that PRN1371 demonstrates time-dependent enzyme inhibition of FGFR1-4 and sustains inhibition of fluorescent probe binding to the FGFR active site, further validating covalent FGFR engagement (8). CSF1R, the only kinase outside the FGFR family inhibited by PRN1371, was also studied using dialysis.…”
Section: Resultsmentioning
confidence: 55%
“…Guided by structure-based design, several chemical scaffolds coupled to cysteine-reactive warheads were synthesized and characterized. Optimization of an attractive lead series was guided by both an FGFR1 enzyme activity assay and an FGFR1 biochemical occupancy assay that provided a readout on covalent cysteine engagement; the detailed SAR and medicinal chemistry involved in this work has been published elsewhere (8). The effort culminated in the identification of PRN1371 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] As imilard esign strategy using the related pyrido[2,3-d]pyrimidin-7(8H)-one core has led to the clinicalstage irreversible FGFR inhibitorP RN1371 (4). [28] Another recent example of an irreversible inhibitor is the potent and FGFR-selective molecule TAS-120( 5,F igure 1) that inhibits all four family subtypes. [29] TAS-120 is currently under phaseI/II clinical trials (ClinicalTrials.gov identifier NCT02052778) to evaluate safety,m aximum tolerated dosage( MTD),a nd recommended phase 2d ose (RP2D) in patients with confirmed advanced metastatic solid tumoursw ith or withoutF GF/FGFR abnormalities who have failed standard therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Futibatinib demonstrated remarkable selectivity for FGFR among 296 kinases and was found to bind covalently to the FGFR kinase domain. The binding mode of futibatinib to FGFR was shown to be quite different from known reversible ATP-competitive FGFR inhibitors, such as AZD4547, infigratinib, erdafitinib, or pemigatinib, orirreversible FGFR inhibitors such as PRN1371(26,32,36,37). Recent structural analysis of the futibatinib-FGFR complex revealed that futibatinib targets the P-loop in the ATP-binding pocket of the FGFR tyrosine kinase domain, forming a rapid covalent adduct with a unique cysteine upon contact(32).…”
mentioning
confidence: 99%